DEVELOPING A COMIC BOOK OF COVID-19 PREVENTION EDUCATION FOR ELEMENTARY SCHOOL STUDENTS - Rahmat Sanusi; Karunia Yulinda Khairiyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was development research with seven steps of development from Borg & Gall aiming to produce a product, namely the Story Book to Covid Prevention. This study involves three validators, the media validator to assess the appearance of the product, the content validator to assess the material in the book, and the user validator. Small-scale trials involved 30 students, and large-scale trials involved 60 students. Data were collected by using an observation approach, questionnaire sheets, and competency tests with descriptive data analysis techniques. Based on the results of product trials and the assessment of the validator, the results of the assessment were good. Thus, this concluded that the Covid-19 Prevention and Transmission Picture Story Book is feasible and effective to use.